Serum-Thyreoglobulin in der Metastasendiagnostik des differenzierten Schilddrüsenkarzinoms - Müller-Gärtner, H.-W.; Schneider, C.; Tempel, M.-Th. (Nuklearmedizin - NuclearMedicine, 1986)
The diagnostic accuracy of serum thyroglobulin (S-TG) determination as measured under endogenous thyrotropin(TSH)stimulation (ETS) has been investigated in 372 patients with completed therapy for differentiated thyroid cancer. In 51 of these (13.7%) S-TG could be detected by means of the IRMA-technique. In 34 S-TG determination was additionally performed during suppressive thyroxine therapy (SSH): S-TG in SSH was significantly lower as compared with S-TG in ETS (p <0.001). In seven cases with proven metastases S-TG values were pushed below the minimal detection level by SSH. Tumor manifestations with suppressive S-TG were significantly smaller (x͂ = 5 ccm, range 1-25 ccm) than those with non-suppressible S-TG (x͂ = 90 ccm, range 11-125 ccm, p <0.005) and displayed a papillary histology. There was a moderate correlation between S-TG concentration and tumor volume (r = 0.71 ; p <0.001). 21 % (n = 66) of patients with undetectable S-TG in ETS showed 131l-uptake in the thyroid region; 2% (n = 7) had proven metastases. Sensitivity of S-TG determination for the detection of metastases amounted to 82.5% in ETS and 53.3% in SST, specificity was 94.6% in ETS and 99.7% in SST. It is concluded that small metastases of papillary thyroid carcinomas may escape S-TG screening more readily than follicular carcinoma metastases when S-TG concentrations are measured during thyroxine treatment.